Acute Respiratory Distress Syndrome Caused by Occupational Exposure to Waterproofing Spray: A Case Report and Literature Review - Fu, Meng; Feng, Chun-Mei; Cao, Le-Jie; Hu, Xiao-Wen; Xu, Qi-xia; Xia, Huai-Ling; Ji, Zi-Mei; Hu, Na-Na; Xie, Wang; Fang, Yuan; Xia, Da-Qing; Zhang, Jun-Qiang (Frontiers in Public Health, 2022)
Background: Acute respiratory distress syndrome (ARDS), being caused by severe infection, trauma, shock, inhalation of harmful gases and poisoning, is a serious respiratory disease, with acute-onset and high mortality. Timely and accurate identification will be helpful to the treatment and prognosis of ARDS cases. Herein, we report a case of ARDS caused by occupational exposure to waterproofing spray. This is the first case of ARDS without specific pathogens by mNGS as an auxiliary diagnosis, which presents the most comprehensive etiological examination of similar reports. Case presentation: A previously healthy 25 years old delivery man developed hyperpyrexia, chest tightness, cough and expectoration. The symptoms occurred and gradually exacerbated after exposure to a waterproofing spray. The most common chest computed tomography (CT) finding showed diffuse ground glass and infiltrative shadows in both lungs. The diagnosis of ARDS related to waterproofing spray was established on the basis of comprehensive differential diagnosis and etiological examination. The patient achieved a good curative effect after giving a transient glucocorticoid treatment. Conclusions: The diagnosis and different diagnosis of acute respiratory failure for outdoor workers, such as delivery drivers, should consider whether toxic aerosol exposure exist from daily contacts. The case can educate the public that more attention should be paid to avoid exposure to these chemicals by aerosols/ingestion mode and take preventive strategies in occupational environment. The treatment effect of glucocorticoids is significant in ARDS patients with general chemical damage caused by inhaling toxic gases and substances.